Targeting the DP2 receptor alleviates muscle atrophy and diet‐induced obesity in mice through oxidative myofiber transition. Issue 1 (16th December 2022) - Ning, Huying; Ren, Huiwen; Zhao, Yan; Yin, HaiFang; Gan, Zhenji; Shen, Yujun; Yu, Ying
Abstract: Background: Mammalian skeletal muscles consist of two main fibre types: slow‐twitch (type I, oxidative) and fast‐twitch (type IIa, fast oxidative; type IIb/IIx, fast glycolytic). Muscle fibre composition switch is closely associated with chronic diseases such as muscle atrophy, obesity, type II diabetes and athletic performance. Prostaglandin D2 (PGD2 ) is a bioactive lipid derived from arachidonic acid that aggravates muscle damage and wasting during muscle atrophy. This study aimed to investigate the precise mechanisms underlying PGD2 ‐mediated muscle homeostasis and myogenesis. Methods: Skeletal muscle‐specific PGD2 receptor DP2‐deficient mice (DP2 fl/fl HSA Cre ) and their littermate controls (DP2 fl/fl ) were subjected to exhaustive exercise and fed a high‐fat diet (HFD). X‐linked muscular dystrophy (MDX) mice and HFD‐challenged mice were treated with the selective DP2 inhibitor CAY10471. Exercise tolerance, body weight, glycometabolism and skeletal muscle fibre composition were measured to determine the role of the skeletal muscle PGD2 /DP2 signalling axis in obesity and muscle disorders. Multiple genetic and pharmacological approaches were also used to investigate the intracellular signalling cascades underlying the PGD2 /DP2‐mediated skeletal muscle fibre transition. Results: PGD2 generation and DP2 expression were significantly upregulated in the hindlimb muscles of HFD‐fed mice ( P  < 0.05 or P  < 0.01 vs. normal chow diet). Compared with DP2 fl/fl mice, DP2 fl/fl HSA Cre mice exhibited remarkable glycolytic‐to‐oxidative fibre‐type transition in hindlimb muscles and were fatigue resistant during endurance exercise (154.9 ± 6.0 vs. 124.2 ± 8.1 min, P  < 0.05). DP2 fl/fl HSA Cre mice fed an HFD showed less weight gain ( P  < 0.05) and hepatic lipid accumulation ( P  < 0.01), reduced insulin resistance and enhanced energy expenditure ( P  < 0.05) compared with DP2 fl/fl mice. Mechanistically, DP2 deletion promoted the nuclear translocation of nuclear factor of activated T cells 1 (NFATc1) by suppressing RhoA/Rho‐associated kinase 2 (ROCK2) signalling, which led to enhanced oxidative fibre‐specific gene transcription in muscle cells. Treatment with CAY10471 enhanced NFATc1 activity in the skeletal muscles and ameliorated HFD‐induced obesity ( P  < 0.05 vs. saline) and insulin resistance in mice. CAY10471 also enhanced exercise tolerance in MDX mice (100.8 ± 8.0 vs. 68.9 ± 11.1 min, P  < 0.05 vs. saline) by increasing the oxidative fibre‐type ratio in the muscles (45.1 ± 2.3% vs. 32.3 ± 2.6%, P  < 0.05 vs. saline). Conclusions: DP2 activation suppresses oxidative fibre transition via RhoA/ROCK2/NFATc1 signalling. The inhibition of DP2 may be a potential therapeutic approach against obesity and muscle disorders.